Habib Husein Ja'far Al-Hadar's Innovative Da'wah Style Through Social Media - Khafiyah Muslihatun Nisa (Kawakib: Journal of Multidisciplinary Research, 2024)
Modern rhetoric includes a strong memory, high creative and fantasy power, appropriate expression techniques and the power of proof and correct judgment, so it can be concluded that Rhetoric is a field of science that studies or questions how to speak which has a charming appeal, so that people who listen to it can understand and be moved by their feelings. Almost all preachers use interesting rhetoric so that the preaching is conveyed well. According to Habib Husein Jafar: "Dakwah is not only cognitive, but also affective. It's not just a transfer of knowledge, but also morals." Conveying da'wah is not an easy thing, including conveying da'wah to young people. Da'wah does have an art. Habib Husein Jafar's preaching style is known to be integrated, tolerant and non-patronizing. The large number of questions from netizens which are considered "eccentric" is proof that Habib Husein Jafar is rational in answering religious issues but still does not depart from the standards of Islamic law. In his book "The Art of Seducing God". Da'wah is a call, inviting humanity to the path of Allah. As time progresses, the way of preaching is adapted to the sophistication of social media technology. The use of social media for preaching will attract a lot of interest from Muslims, especially among young people or what are usually called millennial children.